Nurturing good governance: The confluence of Patron-Network, Institutional Dynamics, and Tassawuf in a manners of exercising political power - Orlando, Sitti Aisyah; Suffian, Firdausi (Journal of Islamic, Social, Economics and Development, 2025)
The principle of good governance is linked to the value, norms, and culture of society. As articulated by Ghazali, the contemporary societal malaise finds its roots in the government's descent into corruption, therefore the roles of political leadership significant to form a utopian society. The booming of morality issue relates to the behavior of patrons questions their position whether they work for society or work for their ‘pocket’, therefore this paper explains, criticized, and advise the political leadership in exercising their power in a manner of mobilizing the state resources.